Dampak Media Sosial terhadap Struktur Sosial: Tinjauan Sosiologi Komunikasi - Nur Jamila B; Wulan Ramadani; Diva Almaidah S (Jurnal Ilmu Sosial dan Humaniora, 2025)
The rapid development of information technology has transformed the landscape of social communication in society, one of which is through the presence of social media. This article aims to examine the impact of social media on social structures from a sociology of communication perspective, using library research methods. Social media functions not only as a means of information exchange but also as a new space for interaction that influences patterns of social relationships, identity formation, and the dynamics of values and norms within society. The study results indicate that social media has positive impacts in the form of easier access to information, expanded social networks, increased public participation, and spaces for self-expression. However, social media also has negative impacts such as shifting social norms, digital inequality, psychological stress, and opinion polarization. Therefore, a critical approach and adequate digital literacy are needed so that society can respond wisely to the development of social media and maintain social cohesion in community life.